Serum ferritin levels and it’s correlation with cardiac iron overload with the help of cardiac T2* magnetic resonance imaging - Mane, Shailaja V.; Agarkhedkar, Sharad; Upase, Dyaneshwar; Kalekar, Tushar; Sindhura, P. (International Journal of Contemporary Pediatrics, 2021)
Background: Frequent blood transfusions in thalassemia major is associated with iron overload in these patients. To reduce the mortality and morbidity, proper usage of iron chelators is necessary to treat iron overload. Cardiac magnetic resonance imaging (MRI) guides in quantification of iron overload in heart. The purpose of this study is to see the correlation between serum ferritin level and T2* MRI in patients with beta thalassemia major. Methods: Period of the study is September 2018 to September 2020. Total 25 patients diagnosed with β-thalassemia major above 5 years of age were enrolled in the study. They were on regular transfusions. Cardiac T2* MRI was done in these patients and correlated with serum ferritin levels. Results: There was no significant correlation observed between cardiac T2* MRI and serum ferritin values (p=0.66, r=-0.094). Conclusions: Our results showed no significant correlation between serum ferritin and cardiac T2* MRI values. Ferritin alone cannot be used as index of myocardial iron overload in thalassemia major.